The Investigation Of The Metacognitive Awarness And The Academic Achievement About Simple Machine In 7th Grade Students In Primary Education - Ayazgok, Busra; Yalcin, Necati (Elsevier Science Bv, 2014)
The aim of this research is to determine the level of metacognitive awarness and level of academic achievement about simple machine, which is a basic subject in Primary Education Science and Technology Course, and to assess correlation between metacognitive awarness and academic achivement about simple machine. The study was conducted in the second semester of 2010-2011 education year with 7th grade students of ten schools chosen randomly and located in Cankaya, Ankara. The quantative data obtained from the Metacognitive Awarness Inventory (MAI) and Academic Test about Simple Machine were analyzied using quantative analysis. In the quantitative analysis, frequency, mean, standard deviation, percentage, independent sample t-test and multiple lineer regression were used. In addition, the most convenient methods for each of the data were applied. At the end of the research a significant difference was detected in many variables. The analysis of data and diagnoises revealed the following; The significant difference was found between both the academic achievements of girl students and boy students about simple machine which is basic subject in primary education science and technology [t(412)= 3.08, p<.05]. However the significant difference was not found between girl students metacognition awarness and boy students metacognition awarness [t(412)= .708, p>.05]. The positive and medium level correlation was establish between academich achievement about simple machine and metacognitive awarness (r=.353, p<0.05). Acording to analysis of multiple lineer regression, Metacognitive awarness clarify approximately %13 of cumulative variance of academic achivements (R=0.353, R-2=126, p=<.05). (C) 2014 The Authors. Published by Elsevier Ltd.
4th World Conference on Learning, Teaching and Educational Leadership (WCLTA) -- OCT 27-29, 2013 -- Univ Barcelona, Barcelona, SPAIN
Keywords: Education; science; technology